Effects of Pitch Area-Restrictions on Tactical Behavior, Physical, and Physiological Performances in Soccer Large-Sided Games - Gonçalves, Bruno; Esteves, Pedro; Folgado, Hugo; Ric, Angel; Torrents, Carlota; Sampaio, Jaime (Journal of strength and conditioning research, 2017)
Gonçalves, B, Esteves, P, Folgado, H, Ric, A, Torrents, C, and Sampaio, J. Effects of pitch area-restrictions on tactical behavior, physical and physiological performances in soccer large-sided games. J Strength Cond Res 31(9): 2398-2408, 2017-The aim of this study was to identify how pitch area-restrictions affect the tactical behavior, physical, and physiological performances of players during soccer large-sided games. A 10 vs. 9 large-sided game was performed under 3 experimental conditions: (a) restricted-spacing, the pitch was divided into specific areas where players were assigned and they should not leave it; (b) contiguous-spacing, the pitch was divided into specific areas where the players were only allowed to move to a neighboring one; (c) free-spacing, the players had no restrictions in space occupation. The positional data were used to compute players' spatial exploration index and also the distance, coefficient of variation, approximate entropy, and frequency of near-in-phase displacements synchronization of players' dyads formed by the outfield teammates. Players' physical and physiological performances were assessed by the distance covered at different speed categories, game pace, and heart rate. Most likely higher values were found in players' spatial exploration index under free-spacing conditions. The synchronization between dyads' displacements showed higher values for contiguous-spacing and free-spacing conditions. In contrast, for the jogging and running intensity zones, restricted-spacing demanded a moderate effect and most likely decrease compared with other scenarios (∼20-50% to jogging and ∼60-90% to running). Overall, the effects of limiting players' spatial exploration greatly impaired the coadaptation between teammates' positioning while decreasing the physical and physiological performances. These results allow for a better understanding of players' decision-making process according to specific task rules and can be relevant to enrich practice task design, such that coaches acknowledge the differential effect by using specific pitch-position area restrictions.